Bacteriochlorin-containing triad: Structure and photophysical properties. (October 2015) - Grin, Mikhail A.; Toukach, Philip V.; Tsvetkov, Vladimir B.; Reshetnikov, Roman I.; Kharitonova, Olga V.; Kozlov, Anton S.; Krasnovsky, Alexander A.; Mironov, Andrey F.
Abstract: A new theranostic agent of bacteriochlorin family has been synthesized by the reaction between 13 1 -(2-aminoethylcarbamoyl)bacteriochlorin e and N, N' -di(carboxypentyl)dicarboindocyanine dye. The structure of the synthesized conjugate was confirmed by nuclear-magnetic resonance spectroscopy. In the conjugate, the efficient energy transfer from the dye to bacteriochlorin was observed. The yield of this process, which was shown to be ∼94%, allowed the dye still retain its ability to fluoresce. Accordingly, the fluorescence spectrum contained two major bands corresponding to fluorescence of bacteriochlorin (756 nm) and conjugated dye (672 nm). It was observed that the conjugate efficiently photosensitizes formation of singlet oxygen and photodynamic oxygenation of an organic compound. The data suggest that the obtained synthetic conjugate is promising for application in both fluorescence diagnostics and photodynamic treatment of tumors. Graphical abstract: Highlights: Newly synthesized conjugate is promising in both photodynamic therapy and fluorescence diagnostics of cancer. The conjugate three covalently linked subunits: two bacteriochlorin moieties and one dicarbocyanine dye. The structure and conformation of the conjugate was determined by 2D NMR spectroscopy and molecular modelling. Spectral properties indicate no pigment–pigment interaction between the ground states of the dye and bacteriochlorin. Energy transfer (dye – bacteriochlorin) and quenching of singlet excited states by bacteriochlorin chromophores are detected.